Efektivitas Materi Buku Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas VII SMP Dalam Pembentukan Nilai-Nilai Karakter Kristiani - Sry Putri Nofita Manullang; Lince Sihombing; Sabar Rudi Sitompul; Meditatio Situmorang; Dorlan Naibaho (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
The aim of this research is to determine the effectiveness of Christian Religious Education and Character Education book material for class VII SMP students, Revised 2016, published by the Ministry of Education and Culture of the Republic of Indonesia in forming Christian character values. The data consisting of 14 chapters of Christian Religious Education and Character Education book material listed above were analyzed through library research using a qualitative approach method. The results of this research are that the material in the book Christian Religious Education and Character for Grade VII SMP students, Revised 2016, published by the Ministry of Education and Culture of the Republic of Indonesia, is effective in forming Christian Character Values, if the structure of the chapters is reconstructed according to the analytical reference: the fruit of the spirit in Galatians 5:22 -23 is proven by the existence of Christian Religious Education and Character Book material for Class VII Middle School Students which contains material on Christian Character Values in accordance with the reference analysis of Galatians 5:22-23 (fruit of the spirit), namely: 1). Kasih refers to the material in chapter VII, chapter X, and chapter XI changed to chapters I, II, and III, 2). Joy refers to material from chapter VI changed to chapter IV, 3). Peace and Prosperity refers to the material in chapter I and chapter V was changed to chapters V and VI, 4). Patience refers to material in chapter III and chapter IV was changed to chapters VII and VIII, 5). Mercy refers to material in chapter II and chapter VIII was changed to chapters IX and X, 6). Kindness refers to material in chapter XII changed to chapter XI, 7). Loyalty refers to material in chapter IX changed to chapter XII, 8). Meekness refers to material in chapter XIII and chapter XIII, and 9). Self-Mastery refers to material from chapter XIV and remains chapter XIV.